Making agricultural support more objective-oriented: Linear programming approach for Ukraine - Taras Vysotskyi (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
In this article we investigate how to integrate the experience and knowledge of local agricultural experts in order to facilitate more objective-oriented use of the agricultural support funds. For this purpose we apply the Linear Programming methodological approach. Within this approach the model for calculating the optimum allocation of agricultural budget is developed. The evaluations criterions, which are used in the modeling, are derived during the interviews with agricultural experts who work at the Zdolbuniv district agricultural department in Ukraine. The outcomes show that the agricultural support should have been redistributed in a slightly different way from the district perspective. However, the calculated changes in most cases match with the overall development directions in the Ukrainian agricultural support policy. Furthermore, the developed model has proved to be a useful and, at the same time, quite simple in application support tool, which could have been used by the agricultural decision-makers in the process of agricultural support distribution.
Keywords: 330; Agricultural support; impact assessment; Linear Programming.